Role of the Endocannabinoid System in the Central Regulation of Nonmammalian Vertebrate Reproduction - Erika Cottone; Valentina Pomatto; Patrizia Bovolin (International Journal of Endocrinology)
The endocannabinoid system (ECS) has a well-documented pivotal role in the control of mammalian reproductive functions, by acting at multiple levels, that is, central (CNS) and local (gonads) levels. Since studies performed in animal models other than mammals might provide further insight into the biology of these signalling molecules, in the present paper we review the comparative data pointing toward the endocannabinoid involvement in the reproductive control of non-mammalian vertebrates, focussing in particular on the central regulation of teleost and amphibian reproduction. The morphofunctional distribution of brain cannabinoid receptors will be discussed in relation to other crucial signalling molecules involved in the control of reproductive functions, such as GnRH, dopamine, aromatase, and pituitary gonadotropins.